Positron Emission Tomography-Computed Tomography Parameters Predict Efficacy of Immunotherapy in Head and Neck Squamous Cell Carcinomas - Zhang, Songtao; Zhang, Runfang; Gong, Wenbo; Wang, Chao; Zeng, Chen; Zhai, Yifei; Fang, Qigen; Dai, Liyuan (Frontiers in Oncology, 2021)
Background This study aims to assess the association between positron emission tomography-computed tomography (PET-CT) parameters and the response to immune checkpoint inhibitors in unresectable head and neck squamous cell carcinoma (HNSCC). Methods A total of 105 patients receiving immunotherapy (pembrolizumab or sintilimab with/without cisplatin) were retrospectively enrolled in this study; pretreatment data regarding metabolic tumor volume (MTV) and maximum standardized uptake value (SUVmax) were collected. The primary interest of the study was objective response rate (ORR), and the secondary was progression−free survival (PFS). Results The mean total MTV was 40.6 cm3 (range: 8.5–100.3), ORRs in tumors with total MTV of ≥40.6 and <40.6 cm3 were 43.1% and 23.1%, respectively; the difference was statistically significant (p = 0.018). Survival analysis indicated similar PFS rates in the two groups (p = 0.057). The mean total SUVmax was 12.5, ORRs in tumors with total SUVmax ≥12.5 and <12.5 were 40.0% and 26.0%, respectively; the difference was not significant (p = 0.092). Survival analysis reported patients with total SUVmax of ≥12.5 had significantly worse PFS (p = 0.001) than patients with total SUVmax of <12.5. Conclusions In HNSCC, total MTV ≥40.6 cm3 translated into improved clinical response but not into better PFS; total SUVmax had no effect on clinical response, but total SUVmax ≥12.5 was associated with worse PFS.